2013
DOI: 10.1016/j.bbamem.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Progressive stages of mitochondrial destruction caused by cell toxic bile salts

Abstract: The cell-toxic bile salt glycochenodeoxycholic acid (GCDCA) and taurochenodeoxycholic acid (TCDCA) are responsible for hepatocyte demise in cholestatic liver diseases, while tauroursodeoxycholic acid (TUDCA) is regarded hepatoprotective. We demonstrate the direct mitochondrio-toxicity of bile salts which deplete the mitochondrial membrane potential and induce the mitochondrial permeability transition (MPT). The bile salt mediated mechanistic mode of destruction significantly differs from that of calcium, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 65 publications
3
59
1
Order By: Relevance
“…Effi cient mitochondria labeling by Rho-123 on hepatocytes was observed ( Fig. 4B, E ), while DCA-NBD Supplemental Material can be found at: ( 20 ). Previous studies have also identifi ed changes in average membrane fl uidity of isolated mitochondria after exposure to toxic bile acids ( 44 ).…”
Section: Subcellular Distribution Of Bile Acid Derivativesmentioning
confidence: 84%
See 3 more Smart Citations
“…Effi cient mitochondria labeling by Rho-123 on hepatocytes was observed ( Fig. 4B, E ), while DCA-NBD Supplemental Material can be found at: ( 20 ). Previous studies have also identifi ed changes in average membrane fl uidity of isolated mitochondria after exposure to toxic bile acids ( 44 ).…”
Section: Subcellular Distribution Of Bile Acid Derivativesmentioning
confidence: 84%
“…Cytotoxic bile acids have been shown to induce cell death through multiple pathways, depending on their concentrations ( 3,4 ), but the corresponding mechanism of action of these molecules is still highly ambiguous and a matter of much debate, as the target of these molecules has recently been alternatively suggested to be the plasma membrane ( 17 ) or the MOM ( 20 ). Our previous studies have demonstrated that at physiologically active concentrations, cytotoxic bile acids have the potential to modulate the structure of lipid membranes, but only for certain lipidic compositions, namely, in the presence of low concentrations of Chol ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has focused on the role of both bile acids in cell signaling and sterile inflammation in the pathophysiology of cholestasis. Thus, reducing the intracellular content and cytotoxicity of bile acids (and other potentially toxic cholephilic compounds that accumulate after secretory failure) is very important for the prevention of cholestatic liver injury [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%